Analisis Perbedaan Kinerja Sosial Dengan Indeks Islamic Social Reporting (ISR) pada Perbankan Syariah Yang Ada di Indonesia dan Malaysia - Aprilia Dwi Widayati; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to examine the difference of Islamic Social Reporting (ISR) disclosure level of islamic banking in Indonesia and Malaysia based on ISR index. The samples were selected by purposive sampling method. The samples that is used in this research is five islamic banks in Indonesia and five islamic banks in Malaysia. This research uses secondary data, that is annual report from 2010-2012. Annual reports were analyzed using content analysis method. Furthermore, the differences of ISR disclosure level were tested using independent sample t-test. The results showed that ISR disclosure level of islamic banking in Indonesia is better than ISR disclosure level of islamic banking in Malaysia. Basedon the results of hypothesis testing, found that there are significant differences in the disclosure level between islamic banking in Indonesia and Malaysia.